Metastatic bladder cancer forming a sigmoidorectal fistula after enfortumab vedotin therapy: a case report - Tamada, Shinji; Ikarashi, Daiki; Yanagawa, Naoki; Toyoshima, Moe; Takahashi, Kenta; Matsuura, Tomohiko; Maekawa, Shigekatsu; Kato, Renpei; Kanehira, Mitsugu; Takata, Ryo; Obara, Wataru (Frontiers in Oncology, 2023)
We report the case of a 68-year-old man who developed a sigmoidorectal fistula after marked response to enfortumab vedotin for advanced bladder cancer. The patient had undergone radical cystectomy with ileal conduit after neoadjuvant chemotherapy. Six months after surgery, local recurrence in the pelvic cavity and multiple lung metastases were found, and the patient was administered pembrolizumab as second-line therapy. Due to worsening local recurrence and suspected invasion of the sigmoid colon and rectum, enfortumab vedotin was initiated as third-line therapy and comprehensive genomic profiling was simultaneously performed. Enfortumab vedotin was remarkably effective, the lung metastases disappeared, and the local recurrent lesion shrank in volume although a sigmoidorectal fistula was found to form through the tumor cavity. Immunohistochemical analysis of the tumor specimens exhibited increased nectin-4 expression. This rare case of metastatic bladder cancer with sigmoidorectal fistula associated with effective enfortumab vedotin therapy suggests that nectin-4 expression and comprehensive genomic profiling might be useful in predicting treatment response to enfortumab vedotin.